Gerakan radikalisme dalam Islam: Perspektif historis - Khadroh, Nurul (Maliki Interdisciplinary Journal, 2023)
He time of the caliph Ali bin Abi Thalib. evidenced by the existence of violence in achieving its goals. In contemporary masses, the Khawarij Group is no longer there, but its mindset continues to carry along with the development of Islam. With the many movements that legalize violence under the pretext of upholding religion. Radicalism in the modern era today can be mapped into two namely radicalism in religion and radicalism in politics. This analysis was written by examining written sources related to radicalism. Some terms of Islamic radicalism will also be explained, the roots of radicalism in Islam, and Islamic radicalism in the contemporary era. In order for radicalism to be more focused, it is taken examples of radicalism in Indonesia.